Global Religions and International Relations: A Diplomatic Perspective - Ferrara, P. author. aut Link
XII, 127 p. 2 illus.
Keywords: With a religious re-emergence in international relations, this book provides an introduction to the role religions play within the global political arena. Culled from theoretical, practical, and real-world experiences, Ferrara explains the role religion now plays in global affairs on diplomatic and political levels.